PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA ABNORMAL RETURN - Krisdiyanti Putri, Made Erika; Nyoman Budiasih, I Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.09.TAHUN 2019DO - 10.24843/EEB.2019.v08.i09.p02, 2019)
The population in this study were all manufacturing companies listed on the Stock Exchange from 2013 - 2017. The sampling technique was carried out using a purposive sampling method that is non-random selection of information obtained using certain considerations. The research sample consisted of 60 manufacturing companies listed on the Indonesia Stock Exchange (IDX) which were sampled during the 2013-2017 period. The measurement of CSR disclosure is based on the Global Reporting Initiative (GRI) -G4 of 91 CSR disclosure index items. Whereas, abnormal returns are calculated using the market adjusted model. The results show that disclosure of CSR affects abnormal returns. Research shows that investors consider CSR information to make decisions. The implication of this research is that investors care about corporate social responsibility in making decisions to invest.